1985
DOI: 10.7557/2.5.2.546
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of the cysts of Sarcocystis rangi from skeletal muscle of reindeer (Rangifer tarandus tarandus)

Abstract: Summary: Mature muscle cysts of Sarcocystis rangi from Rangifer tarandus were examined by transmission electron microscopy. The long and slender cysts were located within skeletal muscle cells, and were bounded by a unit membrane, the cyst membrane. The cysts were provided with closely spaced flexible, hairlike surface processes, measuring up to 12.6 |im in length and 0.3 to 0.6 \lm in diameter. The projections had a smooth surface, whereas the cyst membrane formed numerous hexagonally packed vesicular invagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…However, by SEM the processes could be seen to be more numerous and more orderly distributed over the cyst surface than the TEM images would suggest. Moreover, SEM clearly showed that the cyst processes of S. rungi differed markedly in configuration from those of S. grueneri, as emphasized previously (9). However, it is evident that the cysts of S. rangi are very similar in surface morphology to the cysts of S. cruzi (syn.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…However, by SEM the processes could be seen to be more numerous and more orderly distributed over the cyst surface than the TEM images would suggest. Moreover, SEM clearly showed that the cyst processes of S. rungi differed markedly in configuration from those of S. grueneri, as emphasized previously (9). However, it is evident that the cysts of S. rangi are very similar in surface morphology to the cysts of S. cruzi (syn.…”
Section: Discussionsupporting
confidence: 73%
“…The hair-like configuration of the cyst surface processes of S. rangi was also evident by TEM, as was the hexagonal packing of the minute invaginations of the cyst surface between the bases of the projections (9). However, by SEM the processes could be seen to be more numerous and more orderly distributed over the cyst surface than the TEM images would suggest.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Colwell and Mahrt (1983) complemented the species description and assigned the name S. alceslatrans to the type A cysts that they previously had described grossly and by TEM (Colwell and Mahrt 1981). Transmission electron micrographs presented in their paper from 1981 reveal that these cysts have hairlike protrusions running along the surface of the cysts, similar to those of S. rangi of reindeer (Gjerde 1985d), Sarcocystis sybillensis of elk/wapiti (Dubey et al 1983) and…”
Section: S Scandinavica In Skeletal Musclementioning
confidence: 95%
“…Usually, Sarcocystis species are specific for their intermediate hosts; however, the occurrence of unusual Sarcocystis species in ruminants has been reported (Böttner 1984, Gjerde 1985, Novak and others 1987, Odening and others 1996. To the authors' knowledge, this is the first report of S gracilis-like sarcocysts in sheep, and this might be attributed to adaptation by the parasite to a new intermediate host during the extinction of its natural intermediate host on Sicily.…”
mentioning
confidence: 99%